Probiotics in dentistry: A boon or sham - Rahul Chopra; Shivani Mathur (Wolters Kluwer Medknow Publications, 2013)
Probiotics are dietary supplements, which have been advocated for the prevention and the treatment of a wide range of diseases. These products consist of beneficial micro-organisms, which stimulate health promoting flora thus, suppressing the pathologic colonization and disease spread. Since, probiotics are now widely used in both medical (such as cancer risk reduction, gastrointestinal tract health, and urinary tract health) and dental specialties (reduction in caries development, in achieving periodontal health, reducing oral malodor, etc.), a thorough understanding of their risks and benefits are essential. This review focuses on the recent trends in use of probiotics in dentistry as well as the potential risks associated with them.